FOXO3 targets are reprogrammed as Huntington's disease neural cells and striatal neurons face senescence with p16INK4a increase. Issue 11 (6th November 2020) - Voisin, Jessica; Farina, Francesca; Naphade, Swati; Fontaine, Morgane; Tshilenge, Kizito‐Tshitoko; Galicia Aguirre, Carlos; Lopez‐Ramirez, Alejandro; Dancourt, Julia; Ginisty, Aurélie; Sasidharan Nair, Satish; Lakshika Madushani, Kuruwitage; Zhang, Ningzhe; et al.
Abstract: Neurodegenerative diseases (ND) have been linked to the critical process in aging—cellular senescence. However, the temporal dynamics of cellular senescence in ND conditions is unresolved. Here, we show senescence features develop in human Huntington's disease (HD) neural stem cells (NSCs) and medium spiny neurons (MSNs), including the increase of p16 INK4a, a key inducer of cellular senescence. We found that HD NSCs reprogram the transcriptional targets of FOXO3, a major cell survival factor able to repress cell senescence, antagonizing p16 INK4a expression via the FOXO3 repression of the transcriptional modulator ETS2. Additionally, p16 INK4a promotes cellular senescence features in human HD NSCs and MSNs. These findings suggest that cellular senescence may develop during neuronal differentiation in HD and that the FOXO3‐ETS2‐p16 INK4a axis may be part of molecular responses aimed at mitigating this phenomenon. Our studies identify neuronal differentiation with accelerated aging of neural progenitors and neurons as an alteration that could be linked to NDs. Abstract : Increasingly pronounced senescence features develop in human Huntington's disease (HD) neural stem cells and striatal neurons, including the increase of p16 INK4a . The FOXO3/ß‐catenin complex can oppose these cellular senescence features via transcriptional reprogramming in a Ryk‐dependent manner, antagonizing p16 INK4a expression via the repression of the transcriptional modulator ETS2. The HD brain neural lineage may thus face a continuous senescence process.